Scrotal measurements and visual scores of boar testicle size correlated with testicle weight - Davis, Duane L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Scrotal measurements and visual scores of testicle size were determined for 59 boars used in nutrition and physiology studies. The best predictors of testicular weight were visual scores (average of 3 observers) and partial-circumference measurements. Though visual score was an accurate predictor within groups scored at the same time, it was not a dependable predictor when it included combined scores of groups scored at different times.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Scrotal measurements; Visual scores; Boars; Testicle weight